EMPLOYEE PERFORMANCE IN TERMS OF COMMUNICATION, WORK ETHIC, QUALITY OF WORK LIFE, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT A HOTEL IN PURWOKERTO - Falsafatul Yuri Azizah; Suyoto Suyoto; Fatmah Bagis; Dian Widyaningtyas (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the influence of Communication, Work Ethic, Quality of Work Life (QWL), and Organizational Citizenship Behavior (OCB) on Employee Performance at Hotel Java Heritage Purwokerto. This research was conducted to address performance inconsistencies, communication gaps, and unstable work outcomes, indicating the need to explore internal factors affecting employee productivity.Methods: A quantitative approach using accidental sampling was applied, involving 105 employees as respondents. Data were collected offline through a questionnaire containing 34 indicator items. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 3.0.Results: The findings reveal that Communication and OCB have a positive and significant effect on Employee Performance. Work Ethic shows a positive but non-significant effect, while QWL shows a negative but non-significant effect. These results indicate that strong communication and appropriate extra-role behavior can enhance performance, whereas work ethic and QWL do not directly improve employee outcomes.Conclusion and suggestion: This study highlights the importance of strengthening communication channels and supporting constructive OCB to improve performance. Although Work Ethic and QWL do not show significant effects, they remain relevant and require attention through training, motivation, and work environment enhancement. Future research is recommended to increase the sample size, include multiple hotels, and add moderating variables such as job satisfaction or leadership style to achieve a more comprehensive understanding of performance determinants. Keywords: Communication, Employee Performance, Organizational Citizenship Behavior, Quality of Work Life, Work Ethic,